SEPTUM VAGINA TRANSVERSA - Bobby Indra Utama; Ermawati Ermawati (Andalas Obstetrics And Gynecology Journal, 2019)
The vagina is a membranous muscular tube that connects the vulva and uterus. Congenital or congenital abnormalities in the form of complete or partial absence of the vagina (vaginal agenesis). Patients who experience vaginal agenesis have less frequency, namely 1 in 4000 births, 1 in 4000 to 10,000 births (ACOG). Meanwhile in Dr. Cipto Mangunkusumo Jakarta from 1995 to 1999, an average of 10-12 cases per year. It has been reported the case of a female patient aged 14 years who entered the Gynecology Ward Dr. M. Djamil Padang on January 25, 2014 at 11.00 WIB with a delivery from the RSMJ gyn clinic with a diagnosis of transverse vaginal septum + hematometra + hematotrachelos + hematokolpos planned for a septal incision. After performing the operative action, ± 500 cc of blackish brown liquid was successfully removed.Keywords: Agenesis Vagina, TVS, Tranverse Septum Vagina, Case Report